Screening for depression in old age: A comparison of the geriatric depression scale and the depression in old age scale Depressionsscreening im Alter: Ein Vergleich von geriatrischer Depressionsskala (GDS) und Depression im Alter-Skala (DIA-S) - Wunner, Christina; Stemmler, Mark; Masuch, Johanna; Gosch, Markus; Waller, Christiane; Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2021)
Objective: Since 1996, older patients have been treated in the Nuremberg Geriatric Day Hospital. The geriatric depression scale (GDS) is an obligatory part of the geriatric assessment at admission but its use in the clinical setting has revealed some problems. The aim of the study was to compare the GDS with the depression in old age scale (DIA-S) in terms of applicability and psychometric characteristics. Methods: As gold standard a semi-structured interview was used to record the depression criteria according to Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Using a sample of 375 patients, sensitivity and specificity as well as positive and negative predictive values were calculated for both screening tests. Results: No clear superiority of any screening method could be proven. The sensitivity of the DIA‑S in the overall sample was higher than that of the GDS, but the specificity was much lower. In terms of predictive values, there were slight advantages for the GDS. In the sub-samples, poorer values were found in both scales for cognitively impaired or dementia patients with slightly better values for GDS. Conclusion: The DIA‑S can be used very easily in everyday clinical practice, but no advantages of this method compared to GDS could be demonstrated.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Depressive; Major depression; Older adults; Sensitivity; Specificity

Simplified Screening for Depression in Acutely Hospitalized Geriatric Patients: Comparison of the Two-Item Whooley Questions With the Geriatric Depression Scale-15 - Trabert, Johannes; Bauer, Elena; Golbach, Rejane; Jekel, Katrin; Wunner, Christina; Singler, Katrin; Schütze, Sandra (International Journal of Geriatric Psychiatry, 2025)
OBJECTIVE: The aim of the study is to investigate sensitivity and specificity of the two-item Whooley questions compared to the 15-item Geriatric Depression Scale (GDS-15) for the detection of depressive symptoms in acutely hospitalized geriatric patients. METHODS: Patients were prospectively recruited. Two-item Whooley questions and GDS-15 were performed within 24 h of admission, the GDS-15 being part of the routine geriatric assessment. Montgomery-Asberg Depression Rating Scale (MADRS) served as gold standard in the form of a structured interview which was performed within 48 h of admission. In addition, all patients were examined for independence (Barthel Index), cognition (mini-mental status examination), vision and hearing (finger rub test) and multimorbidity (Charlson Comorbidity Index). RESULTS: 248 patients were recruited. Median (Q1/3) age was 83 (/3 79/86) years, 157 patients (63%) were female. Whooley questions had a sensitivity of 0.95 (95% CI: 0.81-0.99) and specificity of 0.49 (95% CI: 0.43-0.56) identifying moderate depressive symptoms (MADRS ≥ 20 points) with a negative predictive value (NPV) of 0.99. This is compared to a sensitivity of 0.57 (95% CI: 0.37-0.75) and specificity of 0.62 (95% CI: 0.56-0.68) using GDS-15 to identify moderate depressive symptoms. Both functional impairment and cognitive deficits had an impact on the result of GDS-15, but did not influence the result of Whooley questions. CONCLUSIONS: Compared to the GDS-15, the two-item Whooley questions are more accurate to screen for symptoms of depression in acutely hospitalized geriatric patients.
CRIS-Team Scopus Importer:2025-05-09
Keywords: assessment; CGA; depression screening; GDS‐15; MADRS; whooley questions